2009
DOI: 10.4103/0974-1208.51336
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical features and health manifestations in lean vs. obese Indian women with polycystic ovarian syndrome

Abstract: AIMS:To study the prevalence of clinical manifestations in obese and lean polycystic ovarian syndrome (PCOS) women and their health hazards.SETTINGS AND DESIGN:This prospective study was carried out in a tertiary care infertility clinic from 1.7.2005 till 31.12.2007.MATERIALS AND METHODS:These women were diagnosed to have PCOS by the European Society of Human Reproduction and Embryology and the American Society of Reproductive Medicine, Rotterdam 2003 criteria. They were further divided into two groups accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 26 publications
6
17
0
Order By: Relevance
“…The prevalence of HA in Indian PCOS women is reported to be 74.2% vs. 50.6% in obese and non-obese subjects, respectively. [11] In the present study we found the prevalence of HA as 66.67% vs. 60% in obese and non-obese subjects, respectively.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The prevalence of HA in Indian PCOS women is reported to be 74.2% vs. 50.6% in obese and non-obese subjects, respectively. [11] In the present study we found the prevalence of HA as 66.67% vs. 60% in obese and non-obese subjects, respectively.…”
Section: Discussionsupporting
confidence: 54%
“…The authors have reported prevalence of menstrual irregularities as 79.2% vs. 44% in obese vs. non-obese women. [11] In the present study, we are reporting the prevalence of oligomenorrhea as 66.67% in obese and 60% in non-obese women. In the present study, 44.68% married PCOS women complained of infertility [Table 3].…”
Section: Discussionmentioning
confidence: 71%
“…revealed the prevalence rate of obesity to be 37.5%. [13] Lim et al . in a systemic review and meta-analysis concluded that women with PCOS had a greater risk of overweight, obesity, and central obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of obesity and overweight women in the present study was 30% and 40%, respectively. A study conducted by Majumdar et al revealed the prevalence rate of obesity to be 37.5% [11]. Ramanand et al reported irregular cycles in 100% of their study participants, whereas infertility was present in 21% [12].…”
Section: Discussionmentioning
confidence: 90%